Social comparison and energy conservation in a collective action context: A field experiment - Serhiy Kandul; Bruno Lanz; Ghislaine Lang (University of Neuchâtel, Institute of Economic Research (IRENE), 2019)
This field experiment quantifies the impact of social norm information on the demand for indoor temperature. Based on high-frequency data from indoor temperature monitors, we provide participating households with a comparison of average temperature in their apartments relative to that measured in a control group. For more than 90 percent of participants, financial benefits of energy savings are only indirect, as building-level heating costs are shared across apartments in proportion to their volume. Despite the associated collective action problem, we estimate that the intervention induces a -0.28 C reduction in average indoor temperature. This suggests that direct monetary incentives is not a pre-requisite for social comparison feedback to induce energy savings.
Keywords: C91; D12; D62; D91; H41; Q41; 330; Informational intervention; Monetary incentives; Energy saving; Social comparison feedback; Social norms